Women of the Sandwich Generation in Malaysia. - Norzareen, M.; Nobaya, A. (2010)
The aim of this paper is to convey the ideas and concept of the Sandwich Generation in Malaysia in order to educate the readers about this terminologically which is still an unfamiliar term in the society. It focuses on the new trend of family responsibilities, specifically for women, which is care-giving to the elderly. Sandwich Generation refers to a family member that simultaneously has commitments in raising their children, and provides a care-giving support for the elderly parents. Most of the studies which focus on women discuss the issues of work-family conflict, referring to balancing role of women as mothers and employees. However, this paper will discuss about women of the Sandwich Generation that is women who has additional role of caring for their elderly. The first part describes the facts and some characterization of the Sandwich Generation. The second part will discuss the prevalence of aging population, worldwide. Next, this paper will discuss about the multiple roles amongst women in Malaysia. The roles that Malaysian women currently are dealing with are as a primary caregiver, as a wife, mother and as an employee. The final part of this paper is about the well-being of Sandwich Generation women in Malaysia. This paper hopes to provide information on the unique characteristics derived from a new term in a family relationship. The key point of this publication is women as family members who have to provide care to both their aging parents and their children; which are referred to as the Sandwich Generation.